PERTUMBUHAN POPULASI DAPHNIA PADA LIMBAH BUDIDAYA IKAN LELE SISTEM BIOFLOK DENGAN KONSENTRASI BERBEDA - Ardiansyah Kurniawan; Laras Maharani; Robin Robin (Universitas Muhammadiyah Gresik, 2022)
Daphnia sp. is one type of zooplankton that is used as natural food. The potential for catfish culture waste from the biofloc system is not yet known as a source of nutrients in the culture of Daphnia sp. The biofloc system of catfish culture wastewater needs to be tested as a medium for Daphnia cultivation. This research method uses experimental methods, namely experiments and Completely Randomized Design (CRD) methods with 5 treatments and 3 replications, namely control treatment (clean water + chicken manure 5gram/liter), 75% clean water + 25% wastewater, 50% clean water + 50% wastewater, 25% clean water + 75% wastewater, and 100% wastewater. Nitzschia and Melosira from Class Bacillariophyceae and Copepods from Class Maxillopoda were identified in the waste. The use of catfish culture waste in biofloc systems with different concentrations affected the growth of Daphnia sp. Daphnia sp. cultivation media. with a concentration using 75% of the waste produced the highest growth peak on the twelfth day.